Efficacy and Safety of Tripterygium Glycoside in the Treatment of Diabetic Nephropathy: A Systematic Review and Meta-Analysis Based on the Duration of Medication - Li, Yizhen; Miao, Runpei; Liu, Yixing; Zhang, Jiawei; Dou, Zhili; Zhao, Lei; Zhang, Yunan; Huang, Zhe; Xia, Ye; Han, Dongran (Frontiers in Endocrinology, 2021)
Aim Assess the clinical efficacy and safety of Tripterygium Glycosides (TG) after 3-month and 6-month treatment of Diabetic Nephropathy (DN), resolve the confliction between medicine guidance and clinical practice. Methods We conducted a systematic review and meta-analysis of randomized controlled trials of TG in treating DN. We searched PubMed, Cochrane Library, CNKI, VIP, Wan-Fang, CBM, Chinese Clinical Trial Registry and WHO International Clinical Trial Registration Platform till November 2020 and grey literature. Based on the preset inclusion and exclusion criteria, documents screening, quality assessment of methodology, data extraction were conducted by two researchers separately. The methodological quality was assessed by the Cochrane risk test from the Cochrane Handbook 5.2, then eligible literatures were analyzed by Review Manager 5.3 (Rev Man 5.3). The quality of output evidence was classified by GRADE. Results 31 studies (2764 patients) are included. Results show similar significantly decrease in the 24h-UTP and blood creatinine level both in 3-month and 6-month treatment combined with TG comparing with the basic treatment. But to the contrary of the included studies, our results show occurrence of adverse reaction (AR) significantly higher in the TG group; As treatment with TG continued from 3 months to 6 months, the total AR ratio varies little, but percent of severe ARs increased. GRADE indicate that the quality of evidence for adverse reactions was moderate, while that for 24h-UTP and blood creatinine were low. Conclusion Treatment combined with TG could significantly decrease the indicators for DN, while will also cause ARs as the medicine guidance indicated. But even in 3-month, severe AR can get to a high percent, and would increase as treatment with TG continues, thus less than 3 continuous months may not be an appropriate time to avoid ARs; In clinical more attention should be paid to the these severe ARs even in a course normally considered safe, and more high-quality studies are required to give more insights into the balance between the efficacy and safety of TG application in DN.